Bridging Justice Systems: Asset Confiscation in Anti-Corruption Law and Islamic Jurisprudence - Tedhalosa, Adhing; Nugroho, Hibnu; Raharjo, Agus; Syahputra, Azmi (UIN Sunan Kalijaga, 2025)
Under Indonesia’s Anti-Corruption Law, asset confiscation is treated as a civil and in personam matter, further impeded by parliamentary opposition to the Asset Forfeiture Bill. This article examines deficiencies in Indonesia’s asset recovery framework through a comparative legal analysis with Islamic jurisprudence. Employing a critical–comparative approach, the study conducts a normative analysis of Law No. 20 of 2001 on Corruption Eradication, Law No. 8 of 2010 on Money Laundering, the Draft Asset Forfeiture Bill, and Law No. 1 of 2023 (the new Criminal Code), alongside Islamic legal sources. Anchored in the Islamic principle of radd al-maẓālim (the restitution of unjustly acquired wealth), the findings reveal that corruption encompasses both criminal and civil aspects. The study contends that the adoption of a non-conviction-based forfeiture mechanism—underpinned by a calibrated reverse burden of proof and robust judicial safeguards—could substantially improve Indonesia’s capacity for asset recovery. In practical terms, this research highlights the imperative of enacting comprehensive asset confiscation legislation as a fundamental component of Indonesia’s anti-corruption reforms.